Scrolls of love : reading Ruth and the Song of songs - Hawkins, Peter S.; Stahlberg, Lesleigh Cushing (Fordham University Press, 2006)
Respectful of traditional biblical scholarship, this collection of essays aims to move beyond it. It brings together two communities that have read their Bibles in isolation from one another, in ignorance of the richness of the other's traditions.